GROWTH RESPONSE OF TOBACCO WITH APPLICATION OF LIQUID ORGANIC FERTILIZER - Susan Barbara Patricia SM; Setiyono Setiyono; Oria Alit Farisi; Prambudi Arya Pamungkas (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2022)
Utilization organic fertilizers is one of the efforts from agricultural sector to preserve the environment. The application of organic fertilizer not only reduces the use of inorganic fertilizers but also reduces the accumulation of waste and increases the quality of crop yields at the right dose and type. This study utilizes waste substrate from straw mushroom growing media as a mixture plant medium for Tobacco. The fertilizer used is made from liquid coffee waste, cow urine, goat urine, and Kipahit plants. The purpose of this study was to determine the pH, NPK content, C-organic liquid organic fertilizer, determine the effect of the application of liquid organic fertilizer on the growth of Tobacco, and the content of dissolved protein, carbohydrates, and total chlorophyll in Tobacco. The results of laboratory analysis showed the pH value of liquid organic fertilizer meets the Minimum Technical requirements of Organic Fertilizer, Biological Fertilizer and Soil Improver, but the levels of NPK and C-organic do not meet the requirements. Application of liquid organic fertilizer showed a very significant effect on tobacco plant height. The nutrient content of N is strongly correlated with the soluble protein in tobacco plants.